Characterization of functionalized bentonite as nanocarrier of salicylic acid with protective action against Pseudomonas syringae in tomato plants - Mansilla, Andrea Yamila (2020)
Salicylic acid (SA) is a phytohormone with a central role in plant protection against various types of stresses. Exogenous application of SA in plants often requires a fine adjustment of the pH in the applied solution as well as frequent foliar sprays with a rigorous handling of doses. This work investigates the preparation and characterization of nanocomposites composed of bentonite clays (Bent) and SA as bio-active to produce an efficient and stable hormonal formulation to be used in agriculture. Bent-SA was obtained via cationic exchange reactions of natural Bent with an aqueous solution of SA. The physicochemical properties of Bent-SA were studied in terms of Fourier Transform Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD) and Thermogravimetric Analysis (TGA). SA was intercalated in a 3.65% w/w interacting by electrostatic forces between Bent layers. The SA protective activity was investigated in Pseudomonas syringae pv. tomato DC3000 (Pto)-infected tomato plants (Solanum lycopersicum). The expression levels of pathogenesis-related proteins (PRs) were measured by real time quantitative RT-PCR. The genes PR1 and PR5 were up-regulated 2.2- and 1.23-fold, respectively, in 24 h-treated Bent-SA plants. Furthermore, PR3 protein level increased locally and systemically by Bent-SA treatment in plant tissues. The plant disease incidence was significantly reduced in Bent-SA pretreated seedlings. Analyses of DR5:GUS transgenic reporter tomato lines showed that Bent-SA effectiveness was preserved after vehiculization. It was concluded that Bent-SA can provide an environmentally friendly strategy to control tomato plants against Pto bacterial infection.